Dialogicity of Existence in Unanchored Anchorage of Man in Culture - Burda, František (Bohemica Olomucensia, 2015)
Jan Čep both in his work and life experienced and reflected a feeling of lifelong anxiety caused by paradoxical dioecious nature of human existence. At the first sight it could seem that due to anxiety man is hopelessly lonely and closed in a monologue of an unshareable feeling of despair. According to Čep, situation of man in the world is essentially always tragical. The tragical pain of anxiety flows rather from subthreshold awareness of double anchorage of human existence that time to time breaks through on the surface of life via border situations of life. The feeling of Čepian dioecy comes out from revealing of the anthropological nature of an individual, in which man is discovered paradoxically as the one who is more than a mere person, as the one, who is caught out in dialogical relatedness of his whole existence towards the others and towards one's personal Being.
Keywords: Čep's literary works; dialogicity; human existence; dioecy; anxiety